Agents Targeting Apoptosis Take Center Stage in the Battle against Cancer (Journal of Rashid Latif Medical College, 2022)
Effective therapy of cancer requires elimination oftumor cells through programmed cell death orapoptosis, which is a highly regulated process thatavoids the unwanted inflammatory response when cellsdie. Morphologically, the manifestation of apoptosis issimilar across various cell types and species, and isobserved as a series of cellular changes that begin withchromatin condensation, followed by nuclearfragmentation, cell shrinkage, blebbing and finallyphagocytosis1,2. When tumor cells are exposed totherapeutic agents, the damage to cellular organelles ormacromolecules creates substantial intracellularstress, which triggers the onset of the apoptotic celldeath program